THE EFFECT OF THE LEARNING START WITH A QUESTION (LSQ) METHOD TO INCREASE THE THEMATIC LEARNING OUTCOMES FOR CLASS V STATE - Almi Yelli; Desi Desi; Rejeki Rejeki (Indonesian Journal of Basic Education, 2021)
This study aims to determine the effect of learning the Learning Start With A Question (LSQ) method to improve thematic learning outcomes of fifth grade students at SD Negeri 005 Rambah. This research is a classroom action research research. The subjects in this study were students of class V odd semester SD Negeri 005 Rambah for the academic year 2021/2022 as many as 25 students consisting of 11 male students and 14 female students. The data analysis technique used is the method of collecting several instruments in the form of student and researcher activity sheets and question sheets. The results of this study were seen from the first cycle of the first meeting, there were 8 students 32% who reached the KKM. In the first cycle, the second meeting also experienced an increase again, as many as 11 students 44%. In the second cycle of the first meeting, it was found that student learning outcomes increased again from 25 students, 16 (64%) students had reached the KKM. At the second meeting, the results of student learning were very satisfactory, namely from 25 students 22 (88%) . The conclusion of this study is that the application of the Learning Start With A Question (LSQ) method to improve student learning outcomes in thematic subjects of class V SD Negeri 005 Rambah is successful